Spatial distribution patterns and driving factors of ecosystem services and ecological vulnerability in ecologically fragile areas: a case study of the Zhang-Cheng area - Wang, Ye; Xue, Zhong-cai; Ju, An-qi; Yang, Yue; Ren, Wei; Wu, Cai-wu (Frontiers in Ecology and Evolution, 2025)
Integrating ecosystem services (ES) and the ecological vulnerability index (EVI) to analyze the spatial distribution of ecological spaces provides valuable insights into promoting the sustainable development of ecologically fragile regions. To explore the spatial distribution patterns of ES and EVI in such areas, the Zhangjiakou-Chengde (ZC) area was selected as the study region. Four key ES—water yield (WY), soil conservation (SC), carbon sequestration (CS), and food supply (FS)—were assessed, and EVI was evaluated using the Sensitivity-Resilience-Pressure (SRP) model, with Z-score normalization revealing their spatial distribution patterns. The results showed that: (1) ES exhibited an increasing trend, while EVI decreased, with the most significant changes occurring between 2000 and 2010. Spatial patterns revealed that WY, SC, and CS increased from west to east, while FS and EVI decreased, with higher ecological vulnerability in the west; (2) Following Z-score normalization, ES and EVI were categorized into four quadrants: Quadrant I (High ES, High EVI) indicates areas with strong functions but high vulnerability due to human activities and climate change; Quadrant II (Low ES, High EVI) includes arid/semi-arid areas with high restoration potential; Quadrant III (Low ES, Low EVI) covers regions in need of ecological restoration; Quadrant IV (High ES, Low EVI) comprises areas with effective protection and low vulnerability; (3) Climate factors and land use changes significantly impacted the spatial distribution of ES and EVI. Interactions among multiple drivers, particularly in areas with intense human activities, amplified their effects. The findings offer important theoretical support for developing more precise ecological restoration and protection strategies and promoting sustainable development.